Tobacco and risk of oral cancer: a case control study in a tertiary care centre of Dibrugarh district - Chetia, Angchuman; Baruah, Rupali (International Journal Of Community Medicine And Public Health, 2020)
Background: Oral cancer is a disease of antiquity. This chronic disease is a public health problem both in developing as well as developed countries and is among the top three cancers in India. In Assam, some aspects of traditional lifestyle and dietary habits are likely to contribute to the increasing cancer trend. Methods: The hospital-based case control study was undertaken in AMCH, Dibrugarh. Study subjects included were clinically and histopathologically confirmed new cases of oral cancer attending the hospital during the period of June 2018 to May 2019 and equal number of age and sex matched controls. The total sample size including both cases and controls was 116. A predesigned pretested schedule was used for collecting data. Results: Tobacco chewing was the strongest risk factor associated with oral cancer with odds ratio of chewers 6.13 (95% CI, 2.26-16.60). Statistically significant association was seen with duration, age at start, frequency of chewing and retaining tobacco quid overnight. The risk of developing oral cancer was 3.60 times higher (95% CI of (1.45-8.93)) among smokers compared to non-smokers. Conclusions: The incidence of oral cancer is on the rise. Due to the well-established role of lifestyle factors in the development of oral cancer, they should be considered an important cause of avoidable morbidity and mortality in India, and their prevention should be an important target of public health initiatives.